Python kuikku rifarensu dai 4-han / = Python in a nutshell : - Martelli, Alex; Holden, Steve 1950-; McGuire, Paul; Ravenscroft, Anna Martelli (Orairī Japan, 2024)
Python was recently ranked as today's most popular programming language on the TIOBE index, thanks to its broad applicability to design and prototyping to testing, deployment, and maintenance. With this updated fourth edition, you'll learn how to get the most out of Python, whether you're a professional programmer or someone who needs this language to solve problems in a particular field. Carefully curated by recognized experts in Python, this new edition focuses on version 3.10, bringing this seminal work on the Python language fully up to date on five version releases, including preview coverage of upcoming 3.11 features.
Keywords: Python (Computer program language); Python (Langage de programmation)